2021
DOI: 10.1016/j.nrleng.2020.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Encephalopathy and encephalitis during acute SARS-CoV-2 infection. Spanish Society of Neurology's COVID-19 Registry

Abstract: Objectives Since the beginning of the COVID-19 pandemic, the Spanish Society of Neurology has run a registry of patients with neurological involvement for the purpose of informing clinical neurologists. Encephalopathy and encephalitis were among the most frequently reported complications. In this study, we analyse the characteristics of these complications. Patients and methods We conducted a retrospective, descriptive, observational, multicentre study of patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 43 publications
0
17
0
3
Order By: Relevance
“…There were no differences in term of brain MRI abnormalities between severe and mild COVID-19 encephalopathies. However, other reports of neuroimaging abnormalities in COVID-19 associated encephalopathy described cortical or subcortical white matter T2/FLAIR signal hyperintensity as common feature, although in many patients, neuroimaging abnormalities may not be present ( Jain et al, 2020 ; Mahammedi et al, 2020 ; Radmanesh et al, 2020a , Radmanesh et al, 2020b ; Abenza Abildúa et al, 2021 ). Periventricular white matter T2/FLAIR hyperintensity and microbleeds on brain MRI are often attributed to microangiopathy; however, critically ill patients often have severe coagulopathy and severe microangiopathy with several microbleeds ( Maas, 2020 ; Radmanesh et al, 2020b ).…”
Section: Neurologic Manifestations Of Human Coronavirus Infectionmentioning
confidence: 90%
“…There were no differences in term of brain MRI abnormalities between severe and mild COVID-19 encephalopathies. However, other reports of neuroimaging abnormalities in COVID-19 associated encephalopathy described cortical or subcortical white matter T2/FLAIR signal hyperintensity as common feature, although in many patients, neuroimaging abnormalities may not be present ( Jain et al, 2020 ; Mahammedi et al, 2020 ; Radmanesh et al, 2020a , Radmanesh et al, 2020b ; Abenza Abildúa et al, 2021 ). Periventricular white matter T2/FLAIR hyperintensity and microbleeds on brain MRI are often attributed to microangiopathy; however, critically ill patients often have severe coagulopathy and severe microangiopathy with several microbleeds ( Maas, 2020 ; Radmanesh et al, 2020b ).…”
Section: Neurologic Manifestations Of Human Coronavirus Infectionmentioning
confidence: 90%
“…[ 11 ] These studies indicate a proportion of patients are at risk of developing encephalopathy up to 4 weeks after the onset of COVID-19; however, it is not clarified in these reports whether COVID-19 pneumonitis had fully improved at the time when neurologic deficits were observed. [ 2 , 3 , 10 , 11 ] In the present series, acute encephalopathy symptoms developed after recovery from COVID-19 without exacerbation of pneumonitis. In addition, the severity of COVID-19 was moderate or severe although no patients required mechanical ventilation, which differs from the previous report.…”
Section: Discussionmentioning
confidence: 48%
“…[ 1 , 2 , 5 ] According to multicenter study from Spain and Italy, encephalitis, encephalopathy, or acute disseminated encephalomyelitis occurring after four weeks from the onset of COVID-19 was 4 to 8%. [ 2 , 3 ] Ishiyama et al reported that 10 of 12 patients who required ventilation due to COVID-19 developed encephalopathy 38 to 54 days (median, 51 days) after the onset of COVID-19. [ 10 ] In those patients, brain dysfunction, memory disturbance, impaired verbal fluency, and dyscalculia were commonly observed, with tremor seen in 58% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study investigated 841 patients hospitalized with COVID-19 and found that 57% of patients had neurological symptoms ( 69 ). The Spanish Society of Neurology ran a national registry of neurological complications in patients with COVID-19 infection; on the basis of this dataset, a retrospective study investigated patients with encephalopathy or encephalitis ( 70 ). A total of 232 patients were recorded in this dataset, including 51 cases of encephalitis or encephalopathy.…”
Section: Discussionmentioning
confidence: 99%